Granulomatous lesions of the skin - Gautam, K; Pai, RR; Bhat, S (Journal of Pathology of Nepal, 2011)
Background: Granulomatous skin lesions often present as a diagnostic challenge to dermatopathologists due to various modes of presentation and identical histological picture produced by several causes. The aim of the study was to study different granulomatous skin lesions and to determine the relative frequency, the level of clinicopathologic concordance and to compare our results with those of other workers. Materials and Methods: A retrospective analysis of skin biopsies received over a period of two years from January 2007 to December 2008; was performed, and cases of granulomatous dermatitis reported on histopathological examination were reviewed along with special stains. Results: Out of a total of 1590 skin biopsies 106 (6.67%) cases were found to have a granulomatous reaction. It was common in males (63.21%) with most occurring in the fourth to fifth decades. Majority of cases (79 cases, 74.5%) were categorized as infectious granulomatous lesions with predominance of leprosy (63 cases, 79.7%) followed by tuberculosis (6 cases, 7.6%). An overall clinicopathologic concordance was seen in 97% of cases of leprosy. Conclusion: In this study leprosy is the most common cause of granulomatous skin lesions. It can be concluded that histopathology plays an important role in classification of leprosy, and in diagnosis and management of a variety of granulomatous skin diseases. Special stains play a supportive role in infectious granulomas. Keywords: Granulomatous skin lesion; Leprosy; Skin biopsy DOI: http://dx.doi.org/10.3126/jpn.v1i2.5397 JPN 2011; 1(2): 81-86